2011
DOI: 10.1007/s10059-011-0186-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Cold Tolerance of Rice Recombinant Inbred Lines in Low Temperature Environments

Abstract: Low temperature is one of the major environmental stresses in rice cultivation in high-altitude and high-latitude regions. In this study, we cultivated a set of recombinant inbred lines (RIL) derived from Dasanbyeo (indica) / TR22183 (japonica) crosses in Yanji (high-latitude area), Kunming (high-altitude area), Chuncheon (cold water irrigation) and Suwon (normal) to evaluate the main effects of quantitative trait loci (QTL) and epistatic QTL (E-QTL) with regard to their interactions with environments for cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…A total of 179 F8 RILs derived using the single-seed descendant method from a cross between Dasanbyeo (Tongil type, indica) and TR22183 (temperate japonica) developed by Seoul National University in Korea (DT-RILs) were used in this study (Chin et al 2011;Jiang et al 2011). Each RIL was crossed with Dasanbyeo as the female parent, and 178 BC1F1 lines (except for line 40) were produced (BC1F1 line).…”
Section: Plant Materialsmentioning
confidence: 99%
“…A total of 179 F8 RILs derived using the single-seed descendant method from a cross between Dasanbyeo (Tongil type, indica) and TR22183 (temperate japonica) developed by Seoul National University in Korea (DT-RILs) were used in this study (Chin et al 2011;Jiang et al 2011). Each RIL was crossed with Dasanbyeo as the female parent, and 178 BC1F1 lines (except for line 40) were produced (BC1F1 line).…”
Section: Plant Materialsmentioning
confidence: 99%
“…These traits are important in determining yield potential of rice and have been reported to be associated with cold tolerance ability of rice (Jiang et al, 2011;Mackill & Lei, 1997;Zeng et al, 2009). Spikelet fertility was only significantly correlated with panicle number, panicle weight, and culm length (Table 2).…”
Section: Qtls Identified For the Agronomic Traits Under Normal Water mentioning
confidence: 96%
“…Xu et al (2008) identified a QTL (qCTB-10-2) in another cross population in the same interval which explained 14.9% of the total phenotypic variance. Jiang et al (2011) detected a QTL (QTL 10.1) between markers S10001B and S10019 in the same interval which explained 15.9% of the phenotypic variation. The QTL qCTB-10 reported here explains more variation (33%) than qLTSPKST10.1, qCTB-10-2, and QTL 10.1 reported before in other studies.…”
Section: Qtls Identified For the Agronomic Traits Under Normal Water mentioning
confidence: 99%
See 2 more Smart Citations